Application of Multimodal Anesthesia in Surgical Interventions for Lung Cancer - S. V. Kachur; V. T. Dolgikh; O. V. Korpacheva; O. V. Leonov (Общая реаниматология, 2017)
Objective. To prove pathogenically the reasonability of multimodal anesthesia in patients with lung cancer to improve the efficacy of pain management.Materials and methods. 74 patients (59 men and 15 women) aged 46 to 60 years with lung cancer were examined and treated. 42 patients (the main group) underwent surgery under multimodal anesthesia accompanied with epidural blockade, and 32 patients (the comparison group) were subjected to a surgical intervention under inhalation and intravenous anesthesia with mechanical ventilation. The surgeries including atypical lung resection, lobectomy and pneumonectomy were performed. In preoperative, intraoperative and early postoperative periods, the systemic hemodynamics parameters were determined; adrenaline, noradrenaline, dopamine, cortisol, insulin and glucose were measured in plasma, and acidbase balance parameters — in arterial blood. Pain intensity was assessed by the visual analog scale. Data processing was carried out using Microsoft Exсel 2000, STATISTICA6.0 and Biostat software. Normality of distribution was assessed by KolmogorovSmirnov test. Since the ordered sample did not follow the normal distribution law, the data are presented as a median (Me) and interquartile amplitude (25 and 75 percentiles).Results. It has been found that the most significant pathogenic factor in patients being operated due to lung cancer under the standard anesthesia is the expressed activation of the sympathoadrenal system due to the impact of surgical stress. This is manifested by disorders of the central hemodynamic parameters, such as metabolism, nociception and oxygen balance. In surgeries carried out under multimodal anesthesia, the minimal changes of basic homeostasis parameters are registered; these changes are shorttermed, compensated and reversible. Pain syndrome upon completion of surgery and in the early postoperative period is either absent or mild.Conclusion. It is more expedient to perform surgeries to remove malignant tumors in the lungs under the multimodal anesthesia, because these interventions are distinguished by high traumatic rate and having a «fine line» between compensation and decompensation of the basic vital functions in the perioperative period.